KONDISI PSIKOLOGIS PASIEN DAN PENYAKIT KRONIS : LITERATURE REVIEW - Sirli Agustiani; Maya Ardilla Siregar; Raden Bagus Edy Santoso; Ratna Devi (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Chronic diseases require long-term management, are persistent in nature, and may lead to various problems, including psychological issues. Objective: This study aimed to identify the psychological conditions of patients with chronic diseases. Methods: A literature review was conducted using PubMed and Google Scholar databases. Inclusion criteria were full-text articles in English published between 2021 and 2025 discussing psychological conditions in patients with chronic diseases, with participants aged ≥18 years. Articles that were not original research were excluded. Results: A total of 1,658 articles from PubMed and 17,600 from Google Scholar were identified; however, only 5 articles met the inclusion criteria. The findings indicate that patients with chronic diseases experience psychological problems such as depression, anxiety, fear, and stress, which affect social and economic aspects and contribute to feelings of helplessness. Conclusion: Psychological problems in patients with chronic diseases are predominantly characterized by depression, accompanied by anxiety, fear, and helplessness, leading to decreased treatment motivation and quality of life.